An exploration of partnerships in the European automotive industry - Wyatt, Clare Marie (Cranfield University, 2001)
Japanese automakers were the first to gain significant competitive advantage from strong relationships with suppliers. Over the past two decades, Western manufacturers have attempted to follow suit. The mantra of the industry has been collaboration and public attempts have been made to move away from adversarial practices of the 1970s. Partnership has been the most commonly used term to describe collaboration between vehicle manufacturers and their direct suppliers in the West. As yet there is no single, agreed definition of partnership and subsequently the term has been over-used and often abused. Research in the area has been from a range of disciplines and lacks a coherent theoretical framework. The result is a lack of understanding of partnerships and how they operate. In addition, evangelical proponents have generated unrealistic expectations and doubt and scepticism are emerging in the literature. The research described in this thesis explores partnership in the European automotive industry. The aim is to generate new knowledge based on the experience of those involved. ln Stage One the researcher is immersed in a large-scale change initiative implementing partnerships with Nissan and its European supply base in design and development. In Stage Two the researcher explores partnership issues in depth through semi-structured interviews of VM and supplier representatives. The findings suggest that partnership philosophy has yet to be translated into partnership behaviours, that expectations are unclear leading to a reliance on perception rather than reality and that both VMs and suppliers need to assess the balance of investment required to maintain a partnership over time. The research is exploratory and provides the basis for a new, more grounded understanding of partnerships in the European automotive industry.